Research progress of aerodynamic configuration technology of low sonic boom supersonic aircraft - SU Fengnian; ZHONG Ping; ZENG Hui; LUO Yuepei; CHEN Xilan; GUO Chuwei (Hangkong gongcheng jinzhan, 2023)
The aerodynamic configuration of supersonic aircraft has an important effect on the intensity of sonic boom, and the low sonic boom supersonic configuration is the key of the new generation supersonic aircraft, so the aerodynamic configuration of low sonic boom supersonic aircraft is researched extensively. Based on the systematic investigation of foreign sonic boom suppression technologies, six main aerodynamic methods of foreign low sonic boom supersonic aircraft are introduced, including aircraft volume and lift distribution optimization, wing sweep angle change, wing dihedral angle utilization, slender fuselage and wave suppression cone usage, and engine installed on the wing. Four main aerodynamic configuration types of low boom supersonic aircraft are summarized and analyzed. According to the aerodynamic configurations of current supersonic aircraft, it is concluded that the delta configuration is the mainstream aerodynamic configuration of the next generation environmentally friendly aircraft. The development trend of the aerodynamic configuration technologies of low boom supersonic aircraft is prospected.